Radio telescope search for the resonant conversion of cold dark matter axions from the magnetized astrophysical sources - Huang, Fa Peng; Kadota, Kenji; Sekiguchi, Toyokazu; Tashiro, Hiroyuki (Physical review. D, 2018)
We study the conditions for the adiabatic resonant conversion of the cold dark matter (CDM) axions into photons in the astrophysically sourced strong magnetic fields such as those in the neutron star magnetosphere. We demonstrate the possibility that the forthcoming radio telescopes such as the SKA (Square Kilometre Array) can probe those photon signals from the CDM axions.